La violencia simbólica en la narrativa de Indira Córdoba Alberca - Maldonado Jumbo, Josselyn Paola (2024)
Symbolic violence is a concept that Bourdieu develops together with other authors, which falls on the discourse and language that is not conceived as violent but has a load of domination and manipulation. For this violence to take place, it also prioritizes a power relationship between peers, which together with the discourse allows the existence of this violence. For symbolic violence to manifest itself, the discourses and language used normalizes it, perpetuating situations of physical and symbolic violence in spaces such as home, work and society. Spaces in which power relations exist, creating a gap between the dominated and the dominator, whether economic, family, or social. This curricular integration work focuses on the language, discourse, and power relations that the characters in Indira Córdoba Alberca's two anthologies employ towards the protagonists. Nine stories have been chosen, four from Goddesses in the Fire (2007) and five from Hecatombs (2020), from which we have collected different examples of discourse and language that we analyze under three criteria given by Jan van Dijk. These three criteria consist of a) language patterns or the repetition of ideas and/or words; b) the institutions or structures that perpetuate such violence; and c) literal language and discourse. And examples about power relations that we analyzed under Foucault's approach in the economic, social, and family spheres. These examples allowed us to analyze the three foundations of symbolic violence: habitus, social field, and practices of the protagonists, concluding that they were built under the three foundations, reflecting that the secondary characters used a discourse, language and power relations that allowed them to dominate the protagonists, symbolically violating them.